Vo2Max Levels of Modern Ngawi IPSI Pencak Silat Atheles - Vicky Nusa Prasety Zulkarnain; Andy Widhiya Bayu Utomo; Arief Nur Wahyudi (Universitas Muhammadiyah Enrekang, 2024)
A person's ability to consume a lot of oxygen during intense activities, such as exercise, is known as VO2max. The purpose of this study was to determine the VO2max level of Modern Ngawi IPSI pencak silat athletes. This type of research uses a descriptive quantitative approach. This research will produce descriptive data, in the form of written data from populations, subjects and observable objects as research indicators. The sample used in this study were 20 athletes. This data collection technique uses tests and measurements of the MFT Multi-Stage Fitness Test ( Bleep Test ). The results of this study have found that there is an athlete's VO2max level. From the results among the 20 IPSI Modern Ngawi pencak silat athletes have good VO2Max abilities. The results show a maximum score of 51.6 and a minimum score of 36.9, with a mean (mean) of 43.5 and a median of 43.1. Therefore, based on the results of research on the average (mean) and median physical condition, the athlete's VO2Max ability is in the good category.